Capture efficiency of dynamic pH junction focusing in capillary electrophoresis. Issue 9 (31st March 2016) - Wang, Lingyu; MacDonald, David; Huang, Xiaohua; Chen, David D. Y.
Abstract : Dynamic pH junction is one of the techniques used to overcome the issue of poor concentration sensitivity in CE. By introducing a long sample plug in the capillary and focusing the target molecules at the pH boundary between the sample plug and background electrolyte, this focusing technique can achieve a detection limit that is one to two orders of magnitude better than conventional CE. For quantification purposes, the capturing efficiency of the injected molecules should be scrutinized. Focusing of all target molecules inside the sample plug is desired to ensure good linearity across the whole dynamic range. To test the theoretical prediction with a real experiment, nicotine is used as the test molecule for two types of dynamic pH junctions. The first one is with acidic background electrolyte, and can accommodate both optical detection methods and positive‐ion mode mass spectrometric detection, while the other is suitable for optical detection only due to the use of basic separation background electrolyte. With a theoretical simulation study, it is demonstrated that, for either of these dynamic pH junctions, focusing of at least 95% of target molecule injected into the capillary was easily achievable. More importantly, a longer sample plug could generate a high percentage of molecules captured by dynamic pH junction focusing. Sharp, symmetrical peaks and good linearity for calibration curve can be obtained. Real samples with complex matrixes were also used to demonstrate that nicotine can be selectively focused and quantified using CE–MS.